Photoresist for solar cell patterning and preparation method and application thereof
By introducing specific structural units and inorganic fillers into the acrylic resin, combined with leveling agent, a high-resolution, electroplating-resistant photoresist was designed, which solved the problem of insufficient performance of traditional photosensitive inks and realized a thin line-width copper electrode and the improvement of product yield.
Patent Information
- Application Number
- CN202411381333.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
AI Technical Summary
In the patterning process of traditional solar cell electrodes, the resolution and graphical angle performance of the photosensitive ink are insufficient, which cannot meet the demand for thin line-width copper electrodes, and the electroplating resistance is poor, resulting in the electrode width that cannot be less than 20μm, which cannot meet the high precision of the solar industry. and low cost requirements.
A photoresist for solar cells was designed to improve the toughness and strength of the photoresist by introducing long-chain plasticizers, carboxyl groups and structural units into the acrylic resin, and inorganic fillers and streams were introduced into the photoresist. The flat agent controls the proportion of each component to form a high-resolution, steep graphics angle and copper plating-resistant photoresist, suitable for screen printing and electroplating processes.
The high resolution of photoresist is achieved to reach 10μm, the steep straightness of the graphics angle reaches 85-90°, and the copper plating solution is resistant to electroplating, and it is easy to remove glue without residue. It meets the demand for thin line-wide copper electrodes and improves product yield. and process efficiency.
Smart Images

Figure CN119200330A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photoresists, and in particular to a photoresist used for solar cell patterning and a preparation method and application thereof. Background Art
[0002] The electrodes of traditional solar cells need to be screen-printed with conductive silver paste, which forms a grid-like pattern after solidification. Precious metal silver is the main component of conductive silver paste, which has led to the high cost of conductive silver paste and the lack of cost competitiveness of the produced solar cells. In recent years, the research on using cheap metal copper to replace silver as electrodes has become more and more mature. Using copper as the electrode of solar cells requires a graphic process to form the mask coating groove morphology required for copper metal deposition. In the graphic process, the traditional photosensitive ink of the printed circuit board industry is mostly used as the graphic mask material. The resolution and other performance of the photosensitive ink are poor, resulting in low graphic accuracy, the groove width cannot be less than 20μm, and the steepness of the groove sidewall is poor. With the continuous improvement of the efficiency of solar cells, the width of the electrode on the battery needs to be less than 10μm, and even in the near future it needs to be reduced to less than 8μm. This results in the current performance of the photosensitive ink being unable to meet the demand for the development of fine line width in the solar industry.
[0003] With the development of the solar energy industry, one of the difficulties in using copper instead of silver to prepare electrodes for solar cells is to pattern the grooves required for copper deposition, which generally uses five steps: screen printing of photosensitive materials, exposure, development, electroplating of metals, and ink removal. There are strict requirements on the patterning angle (88-90°), development speed, electroplating resistance, and degumming ability of the mask material used for patterning.
[0004] Based on this, there is an urgent need for a photoresist with high resolution after development, steep pattern angle, resistance to copper plating solution, and easy debonding to meet the needs of fine-line copper electrodes for solar cells. Summary of the invention
[0005] To solve the above problems, the present invention provides a photoresist for solar cell patterning and a preparation method and application thereof. The photoresist can be used in the patterning copper electroplating process of solar cell sheets, is suitable for coating by screen printing, has the characteristics of rapid curing and development, and has a maximum resolution of 10 μm after exposure and development. The pattern angle is steep (85-90°), and it is resistant to electroplating with copper electroplating solution, easy to remove without residue, has no effect on subsequent processes, and is conducive to meeting the demand for fine-line copper electrodes and improving product yield.
[0006] Specifically, the following technical solutions are provided:
[0007] The first aspect of the present invention provides a photoresist for solar cell patterning, wherein the photoresist comprises the following components by mass percentage: 45%-65% of acrylic resin, 3%-12% of photoinitiator, 10%-40% of cross-linker, 5%-20% of inorganic filler and 10%-30% of solvent, based on the mass sum of acrylic resin, photoinitiator, cross-linking agent, inorganic filler and solvent; the photoresist composition further comprises a leveling agent, and the concentration of the leveling agent in the photoresist composition is 1000-3000ppm;
[0008] The acrylic resin includes structural units shown in formula I to formula IV:
[0009]
[0010] Wherein, R1 is a hydroxyl group;
[0011] R2 is hydrogen, methyl or ethyl;
[0012] R3 is hydrogen or hydroxyl;
[0013] R4 is methyl, ethyl or phenyl;
[0014] R5 is a C10-C18 alkyl group.
[0015] In order to solve the above technical problems, the present invention obtains a photoresist that can be used for solar cell patterning by designing the acrylic resin structure and improving the photoresist formula. Among them, by introducing a long-chain plasticizer structure (R5) into the structure of the acrylic resin to reduce the Tg value of the resin, the toughness of the photoresist after cross-linking is improved, and the electroplating resistance of the photoresist is improved; in addition, a carboxyl group is introduced into the acrylic resin to ensure the dissolution rate of the photoresist in an alkaline developer, and a structural unit II is introduced to improve the strength of the acrylic resin, so as to form an effective pattern that is not easy to collapse, so as to improve the accuracy of the photoresist, and a structural unit III is introduced to adjust the molecular weight and structural framework of the acrylic resin; under the synergistic effect of the above structural units, the photoresist composed of the acrylic resin has high precision after curing, steep pattern angles, and is resistant to copper electroplating solution electroplating, and is easy to remove without residue.
[0016] In addition, in the photoresist protected by the present invention, each component needs to be controlled within a suitable range, for example, the acrylic resin content needs to be controlled between 45% and 65%. If the content is lower than 45%, the corresponding photoresist has low viscosity and is not suitable for screen printing. If the content is too high, greater than 65%, the film thickness increases after coating, affecting subsequent exposure and development. The photoinitiator content needs to be controlled between 3% and 12%. Too little photoinitiator content will result in too low exposure energy, insufficient crosslinking, and graphic distortion. Too high an initiator content will require high exposure energy and long exposure time, which is not conducive to mass production capacity control. The content of the crosslinking agent will affect the film retention rate of the photoresist before and after filming and the and the resolution after exposure. If the cross-linking agent content is too low, the cross-linking strength will be insufficient and the film retention rate after the photoresist is developed will be insufficient. If the cross-linking agent content is too high, the size will become larger after exposure and the resolution will decrease. Preferably, the cross-linking agent content needs to be controlled within the range of 10%-40%. The solvent in the photoresist is also one of the indispensable components. The solvent content mainly affects the viscosity of the photoresist and the film thickness after coating. If the solvent content is lower than 10%, the viscosity of the prepared photoresist is too high, and the film thickness after coating is too thick, which is not conducive to the exposure and development process. If the solvent content is greater than 30%, the viscosity of the photoresist will be too low and the coating thickness cannot reach the target thickness. In addition, the present invention also introduces inorganic fillers into the photoresist. The introduction of inorganic fillers does not affect the resolution of the photoresist, and can effectively improve the viscosity of the photoresist, making it suitable for coating methods such as silk screen printing and slit coating. However, the mass percentage of the inorganic filler in the photoresist needs to be controlled at 5%-20%. If the content is too low, the viscosity of the photoresist cannot be improved, and the prepared photoresist is not suitable for silk screen printing. If the content is too high, the film thickness formed by coating is too large, affecting the coating uniformity and having an adverse effect on subsequent processes. When the viscosity increases, the fluidity of the photoresist decreases with the increase in viscosity. At this time, it is necessary to add a leveling agent to change the fluidity of the photoresist, thereby solving the coating leveling characteristics of the high-viscosity photoresist. Under the synergistic effect of the above components, the prepared photoresist can be formed into a film with a suitable film thickness of about 10-15μm by screen printing, and the maximum resolution after exposure and development reaches 10μm, the pattern angle is steep (85-90°), and it is resistant to electroplating with copper electroplating solution, and there will be no whitening, plating penetration, and glue falling in the electroplating solution. After the electroplating is completed, the photoresist film layer is cleanly removed in an alkaline stripping solution without any photoresist residue, and there is no impact on subsequent processes.
[0017] Furthermore, the molecular weight of the acrylic resin is 6000-8000, and the molecular weight distribution is 1.6-3.0. Screen printing has high requirements on the viscosity of the photoresist, which needs to reach more than 10000cp. Increasing the molecular weight of the acrylic resin can increase the viscosity of the photoresist, but too high a molecular weight is not conducive to the resolution of the photoresist. Preferably, the molecular weight of the acrylic resin is controlled in the range of 6000-8000, and the viscosity of the photoresist is synergistically improved by introducing inorganic fillers.
[0018] Furthermore, the acrylic resin has the following general structural formula: Wherein, X, Y, M, and N are each independently selected from any integer from 1 to 10; in some preferred embodiments, the acrylic resin is obtained by polymerization of methacrylic acid, p-hydroxystyrene, phenol ethoxy acrylate, and 18 acrylate in the presence of an initiator, and the initiator is preferably azobisisobutyronitrile.
[0019] Furthermore, the photoinitiator is preferably one or more of 1-[4-(phenylthio)phenyl]-1,2-octanedione-2-(O-benzoyl oxime), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime), 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, and 2,2-dimethoxy-1,2-diphenylacetophenone.
[0020] Furthermore, the cross-linking agent is selected from one or more of 2-phenoxyethyl acrylate, ethylene glycol phenyl ether acrylate, and ethoxy bisphenol A dimethacrylate.
[0021] Furthermore, the inorganic filler is selected from one or more of silicon dioxide, activated carbon, and bentonite; the particle size of the inorganic filler is less than 5 μm; in some preferred embodiments, the inorganic filler is silicon dioxide with a particle size less than 2 μm. The addition of small-particle inorganic fillers does not affect the resolution of the photoresist, and this type of inorganic filler does not contain metal ions and has no effect on the electroplating performance. At the same time, it can effectively improve the viscosity of the photoresist, making the photoresist suitable for coating methods such as silk-screen printing and slit coating.
[0022] Furthermore, the solvent is preferably propylene glycol methyl ether acetate and / or propylene glycol methyl ether.
[0023] Furthermore, the leveling agent is silicone acrylate, and the introduction of the leveling agent is mainly used to improve the fluidity of the photoresist. Since the main resin of the photoresist system is acrylic resin, in order to improve the compatibility of the leveling agent with the acrylic resin system, silicone acrylate with good leveling properties and good compatibility with acrylic resin is preferred. The principle of like dissolves like and the ability of the leveling agent to reduce surface tension are utilized to solve the coating leveling properties of high-viscosity photoresist.
[0024] The second aspect of the present invention provides a method for preparing the photoresist described in the first aspect, comprising uniformly mixing a formulated amount of acrylic resin, a photoinitiator, a crosslinking agent, an inorganic filler, a leveling agent and a solvent, and filtering to obtain the photoresist after the acrylic resin is completely dissolved.
[0025] The third aspect of the present invention provides an application of the photoresist described in the first aspect in a solar cell patterning process.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The invention provides a photoresist for solar cell patterning. The photoresist can form a preset pattern on a silicon wafer substrate by coating methods such as screen printing, spin coating, and slit coating. The baked film can reach 2-30 μm, and the highest resolution after exposure and development can reach 2 μm. The morphology steepness of the photoresist reaches more than 85°, and it can resist the corrosion of the plating solution during the electroplating process. The photoresist surface will not turn white, infiltrate, or fall off in the plating solution. After the electroplating is completed, the photoresist film layer can be removed in an alkaline debonding solution, and no photoresist residue is left on the substrate, which does not affect subsequent processes and is conducive to improving the yield of solar cell preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the graphic morphology of the photoresist prepared in Example 1 after development. DETAILED DESCRIPTION
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0030] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0031] The sources of some of the raw materials used in the following examples and comparative examples are as follows:
[0032] Acrylic resin: purchased from Colison Company, model number KN1051F;
[0033] Initiator: 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyl oxime), referred to as OXE-02, purchased from BASF, Germany;
[0034] Initiator: 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, referred to as 907, purchased from BASF, Germany;
[0035] Cross-linking agent: ethoxylated bisphenol A dimethacrylate, purchased from Zhongshan Dixin Chemical Co., Ltd.;
[0036] Solvent: Propylene glycol methyl ether acetate, purchased from Dow Chemical;
[0037] Leveling agent: TEGO-2100, purchased from Digo Company;
[0038] Inorganic filler: Nano-silicon dioxide, purchased from Zhuzhou Xinglong Ultrafine Nanomaterials Co., Ltd.
[0039] Example 1
[0040] This embodiment provides a photoresist for solar cell patterning, and the specific preparation method is as follows:
[0041] Preparation of acrylic resin 1:
[0042] Methacrylic acid, p-hydroxystyrene, phenol ethoxy acrylate, 18 acrylate and azobisisobutyronitrile were weighed according to the mass of 23g, 55g, 15g, 6g and 1g respectively, dissolved in 170g of diethylene glycol solution, added to a 500mL flask, heated in a water bath under nitrogen protection, raised to 70-75°C, and kept warm for 2 hours. After the molecular weight reached the set target value, the heating device was removed, cooled to below 40°C, 0.3g of p-tert-butyl o-benzene was added, and stirring was continued for 1 hour. After cooling to room temperature, the above mixed solution was slowly added dropwise to 1000g of cyclohexane solution. Resin will precipitate under stirring. Stirring was continued for 1 hour, centrifugal filtration was performed, and the solid resin was placed in a vacuum oven at 50°C and dried for 48 hours to obtain a solid acrylic resin with a molecular weight of 7500 and a molecular weight distribution of 1.8.
[0043] Preparation of photoresist: 30g of the above-prepared solid acrylic resin, 5g of photoinitiator (0.1g OXE-02, 4.9g 907), 8g of cross-linking agent (ethoxybisphenol A dimethacrylate), 6g of nano-silica and 8g of propylene glycol methyl ether acetate were added to a feeding kettle, and then 1300ppm of TEGO-2100 was added and stirred for 6h. After dissolution, it was filtered through a 5μm filter element to obtain a photoresist.
[0044] The photoresist prepared in this embodiment contains the following components by mass percentage: 52.6% solid acrylic resin, 8.8% photoinitiator, 14.0% crosslinker, 10.6% inorganic filler (nano-silica), 14.0% solvent (propylene glycol methyl ether acetate), and the concentration of leveling agent (TEGO-210) is 1300ppm.
[0045] Example 2
[0046] This embodiment provides a photoresist for solar cell patterning, which differs from Example 1 only in the formulation of the photoresist, specifically: 30g of the solid acrylic resin prepared in Example 1, 6g of a photoinitiator (0.18g of OXE-02, 5.82g of 907), 16g of a cross-linking agent (ethoxybisphenol A dimethacrylate), 6g of nano-silicon dioxide, 8g of propylene glycol methyl ether acetate and 1500ppm of TEGO-2100, and the remaining operations are the same to prepare a photoresist.
[0047] The photoresist prepared in this embodiment contains the following components by mass percentage: 45.5% solid acrylic resin, 9.1% photoinitiator, 24.2% crosslinker, 9.1% inorganic filler (nano-silica), 12.1% solvent (propylene glycol methyl ether acetate), and the concentration of leveling agent (TEGO-210) is 1500ppm.
[0048] Example 3
[0049] This embodiment provides a photoresist for solar cell patterning, which differs from Example 1 only in the formulation of the photoresist, specifically: 30g of the solid acrylic resin prepared in Example 1, 7g of a photoinitiator (0.28g of OXE-02, 6.72g of 907), 9g of a cross-linking agent (ethoxybisphenol A dimethacrylate), 10g of nano-silicon dioxide, 8g of propylene glycol methyl ether acetate and 1500ppm of TEGO-2100, and the remaining operations are the same to prepare a photoresist.
[0050] The photoresist prepared in this embodiment contains the following components by mass percentage: 46.9% solid acrylic resin, 10.9% photoinitiator, 14.1% crosslinker, 15.6% inorganic filler (nano-silica), 12.5% solvent (propylene glycol methyl ether acetate), and the concentration of leveling agent (TEGO-210) is 1500ppm.
[0051] Example 4
[0052] This embodiment provides a photoresist for solar cell patterning, which differs from Example 1 only in the formulation of the photoresist, specifically: 40g of the solid acrylic resin prepared in Example 1, 4.5g of a photoinitiator (0.25g of OXE-02, 4.25g of 907), 10g of a cross-linking agent (ethoxybisphenol A dimethacrylate), 8g of nano-silicon dioxide, 10g of propylene glycol methyl ether acetate and 1300ppm of TEGO-2100, and the remaining operations are the same to prepare a photoresist.
[0053] The photoresist prepared in this embodiment contains the following components by mass percentage: 55.2% solid acrylic resin, 6.2% photoinitiator, 13.8% crosslinking agent, 11.0% inorganic filler (nano-silica), 13.8% solvent (propylene glycol methyl ether acetate), and the concentration of leveling agent (TEGO-210) is 1300ppm.
[0054] Comparative Example 1
[0055] This comparative example provides a photoresist for solar cell patterning, which differs from Example 1 only in the molecular weight of the acrylic resin. Acrylic resin 2 with a molecular weight of about 30,000 is used, and the other operations are the same to prepare the photoresist.
[0056] Comparative Example 2
[0057] This comparative example provides a photoresist for solar cell patterning. The only difference from Example 1 is the type of acrylic resin. Acrylic acid 8 ester is used instead of acrylic acid 18 ester to prepare acrylic resin 3 (molecular weight is about 7500). The other operations are the same to prepare the photoresist.
[0058] Comparative Example 3
[0059] This comparative example provides a photoresist for solar cell patterning, which differs from Example 1 only in the type of acrylic resin. The acrylic resin used in this comparative example is purchased from Collisson Company, with model number KN1051F and molecular weight of 8000. The other operations are the same to prepare the photoresist.
[0060] Comparative Example 4
[0061] This comparative example provides a photoresist for solar cell patterning, which is different from Example 1 only in that no leveling agent is added, and the other operations are the same to prepare the photoresist.
[0062] Comparative Example 5
[0063] This comparative example provides a photoresist for solar cell patterning, which is different from Example 1 only in that no nano-silicon dioxide is added, and the other operations are the same to prepare the photoresist.
[0064] The formulations of the photoresists prepared in the above examples and comparative examples are shown in Table 1 below:
[0065] Table 1
[0066]
[0067] Application and performance testing
[0068] The photoresists prepared in the above embodiments and comparative examples are used for copper electroplating, and the specific operation is as follows:
[0069] The photoresists prepared in the above embodiments and comparative examples were screen-printed on square PVD copper sheets, baked on a hot plate at 90°C for 150s, and then exposed with an exposure machine. The photoresist layer was developed in 2.38% TMAH (Jingrui Electric Materials), then rinsed with pure water, dried with nitrogen, and then electroplated with copper. After electroplating with copper, the resist was removed (removed with 2-3% NaOH solution after electroplating) to obtain the desired electroplated pattern.
[0070] The following factors are examined:
[0071] (1) Coating film thickness and film thickness uniformity, test coating thickness 10±1μm;
[0072] (2) Graphic CD size. The smaller the CD size, the higher the resolution.
[0073] (3) The steepness of the photoresist morphology (after coating, the photoresist surface is cured by laser, and the part that needs to be removed by development will not be cured by the laser). The closer the angle of the photoresist pattern is to 90°, the better;
[0074] (4) After copper electroplating, observe whether the adhesive surface is plated. If there is no cracking and / or plating, it is "OK".
[0075] The test results are shown in Table 2:
[0076] Table 2
[0077] Test Example Coating film thickness Film thickness uniformity CD Size Steepness Electroplating results Comprehensive Assessment Target 10±1μm ≦9% ≦12μm ≧85° OK OK Example 1 10.4μm 6.72% 10μm 87° OK OK Example 2 10.6μm 7.43% 12μm 88° OK OK Example 3 10.8μm 8.72% 10μm 89° OK OK Example 4 9.5μm 6.72% 9μm 87° OK OK Comparative Example 1 13.7μm 11.72% 16μm 65° Plating NG Comparative Example 2 9.37μm 7.85% 15μm 85° Plating NG Comparative Example 3 11.87μm 7.32% Wire breakage / glue loss 43° Plating NG Comparative Example 4 10.75μm 29.5% 11μm 85° OK NG Comparative Example 5 2.2μm 12.4% 12.5μm 78° OK NG
[0078] As shown in Table 2, the photoresist prepared in Examples 1-4 can be prepared by screen printing to obtain a controllable thickness and uniform adhesive layer, the formed graphics have high resolution, the CD size is less than 12 microns, the graphics angle is steep, the steepness is between 85°-90°, and no plating phenomenon occurs after copper electroplating, which will not have an adverse effect on subsequent processes. The photoresist provided by the present invention is not only suitable for solar cell graphic processing, but also conducive to achieving the demand for fine line width copper electrodes and improving product yield.
[0079] It can be seen from Example 1 and Comparative Examples 1-3 that the molecular weight of the acrylic resin used to prepare the photoresist, the type of monomer, etc. will have a great impact on the performance of the formed photoresist. For example, Comparative Example 1 uses a high molecular weight acrylic resin to prepare the photoresist, and the thickness of the glue layer formed by screen printing is thick and the uniformity is poor. More importantly, the resolution, steepness and electroplating resistance are not up to standard, which seriously affects the product yield. In addition, the alkyl chain in the structural unit IV contained in the acrylic resin used in Comparative Example 2 is relatively short, resulting in a low resolution of the formed pattern and poor electroplating resistance; and the photoresist prepared by using commercially available acrylic resin, the pattern formed by screen printing has the phenomenon of broken wires and glue falling off, and the steepness is only 43°, and the electroplated copper thickness has a seepage phenomenon, which cannot be used in the solar cell graphic process.
[0080] It can be seen from Example 1 and Comparative Examples 4 and 5 that leveling agents and inorganic fillers are also essential components in photoresists. The photoresist prepared in Comparative Example 4 does not contain a leveling agent, and the film thickness uniformity of the adhesive layer formed by screen printing is extremely poor. The adhesive layer formed by the photoresist that does not contain an inorganic filler (Comparative Example 5) is not only too thin but also has a low steepness, and both do not meet the process requirements.
[0081] In summary, the present invention introduces a specific acrylic resin and the synergistic effect between the resin and other components, so that the prepared photoresist can not only form a preset pattern with controllable thickness and good uniformity on a silicon wafer substrate by screen printing, but also has high resolution after exposure and development, good morphology steepness, and can resist corrosion from the plating solution during the electroplating process, and will not cause whitening of the photoresist surface, plating penetration, and film shedding in the plating solution. After the electroplating is completed, the photoresist film layer can be removed in an alkaline stripping solution, and no photoresist residue is left on the substrate. The present invention is suitable for the graphic process of solar cells, can meet the needs of fine-line copper electrodes, and is conducive to improving the product yield.
[0082] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A photoresist for solar cell patterning, characterized in that: Taking the sum of the mass of acrylic resin, photoinitiator, crosslinking agent, inorganic filler and solvent as 100%, the photoresist comprises the following components by mass percentage: 45%-65% acrylic resin, 3%-12% photoinitiator, 10%-40% crosslinking agent, 5%-20% inorganic filler and 10%-30% solvent; the photoresist composition further comprises a leveling agent, and the concentration of the leveling agent in the photoresist composition is 1000-3000ppm; The acrylic resin includes structural units shown in formula I to formula IV: Wherein, R1 is a hydroxyl group; R2 is hydrogen, methyl or ethyl; R3 is hydrogen or hydroxyl; R4 is methyl, ethyl or phenyl; R5 is a C10-C18 alkyl group; X, Y, M, and N are each independently selected from any integer from 1 to 10.
2. The photoresist according to claim 1, characterized in that The molecular weight of the acrylic resin is 6000-8000, and the molecular weight distribution is 1.6-3.
0.
3. The photoresist according to claim 1, characterized in that The acrylic resin has the following general structural formula: Wherein, X, Y, M, and N are each independently selected from any integer from 1 to 10.
4. The photoresist according to claim 1, characterized in that The photoinitiator is selected from one or more of 1-[4-(phenylthio)phenyl]-1,2-octanedione-2-(O-benzoyl oxime), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime), 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, and 2,2-dimethoxy-1,2-diphenylacetophenone.
5. The photoresist according to claim 1, characterized in that The crosslinking agent is selected from one or more of 2-phenoxyethyl acrylate, ethylene glycol phenyl ether acrylate, and ethoxy bisphenol A dimethacrylate.
6. The photoresist according to claim 1, characterized in that The inorganic filler is selected from one or more of silicon dioxide, activated carbon, and bentonite; and the particle size of the inorganic filler is less than 5 μm.
7. The photoresist according to claim 1, characterized in that The solvent is propylene glycol methyl ether acetate and / or propylene glycol methyl ether.
8. The photoresist according to claim 1, characterized in that The leveling agent is silicone acrylate.
9. A method for preparing a photoresist according to any one of claims 1 to 8, characterized in that: The acrylic resin, photoinitiator, cross-linking agent, inorganic filler, leveling agent and solvent in the formulated amount are uniformly mixed, and after the acrylic resin is completely dissolved, the photoresist is obtained by filtering.
10. Use of the photoresist according to any one of claims 1 to 8 in a solar cell patterning process.
Citation Information
Cited By
Photosensitive composition of circuit ink and preparation method thereof
CN121934318A